The general budget and its impact on the investment efficiency of the Iraqi economy for the period 2004-2022 - Kassar, Ali Hasan; Maznan, Nassr Hammood (Edelweiss Applied Science and Technology, 2024)
In order to provide a stable and supportive environment for investment through public budget tools and variables, it is necessary to research methods that lead to stimulating investment operations and providing the necessary financing for economic activity. Total public revenues, total public expenditures, and the budget surplus or deficit have a significant impact on this. Total public revenues and public expenditures have a significant impact on the budget surplus or deficit, which in turn affects investment in the Iraqi economy. In the event of an increase in public revenues, such as an increase in oil or tax revenues, this will lead to an increase in the budget surplus. A higher budget surplus will provide the government with more financial resources to finance public investments and development projects. Achieving the appropriate environment accelerates economic growth and pushes investors to activate their activities, thus expanding their proceeds to form a development horizon and space that creates a broad developmental investment environment to demonstrate the investment opportunities available to investors. If public expenditures rise, such as increased spending on salaries and wages or government purchases, this will lead to an increase in the budget deficit. A high budget deficit will restrict the government's ability to allocate financial resources to finance public investments and development projects. This may negatively affect the investment climate and encourage investors to invest in the Iraqi economy.Therefore, it can be said that managing public revenues and expenditures in a balanced and effective manner has a significant impact on the budget surplus or deficit, which in turn directly affects investment levels in the Iraqi economy.The results of the standard model were obtained using the distributed slowdown autoregressive model (ARDL), which is considered one of the advanced standard methods, which relies on testing the stability of time series. This model gives results about the nature of the relationship in the short term (error correction model) as well as results for the long term. The research reached a set of conclusions, the most important of which is after testing the soundness and... Stability of the estimated model for the variables. The first step after testing the stability of the variables is to estimate the autoregressive distributed lag (ARDL) model for the function of total investments (Y) with lag periods (2) for the dependent variable (Y), the variable (X1) total public revenues as an independent variable, and the variable (X2) total Public expenditures are an independent variable, and the variable (X3) budget surplus is an independent variable. After conducting the model estimation process, we obtained the results for estimating the ARDL model, as the explanatory power of the estimated model was (R2 = 0.817), meaning that the independent variables included in the estimated model explain 81% of the changes in the variable. Follower. The estimated model also turned out to be significant, so the null hypothesis was rejected and the alternative hypothesis was accepted. Also testing the existence of a cointegration relationship between the variables of the model, i.e. the existence of a long-term equilibrium relationship, by testing the limits.